Being 'fun' at work: emotional labour, class, gender and childcare. (25th January 2013) - Vincent, Carol; Braun, Annette
Abstract : This paper reports on data drawn from an Economic and Social Research Council ‐funded project investigating the experiences of UK‐based students training on level‐2 and level‐3 childcare courses. We focus on the concept of emotional labour in relation to learning to care for and educate young children and the ways in which the students' experiences of emotional labour and the expectations placed upon their behaviour and attitudes are shaped by class and gender. We consider the ways in which students are encouraged to manage their own and the children's emotions and we identify a number of 'feeling rules' that demarcate the vocational habitus of care work with young children. We conclude by emphasising the importance of specific contexts of employment in order to understand workers' emotional labour and argue for more recognition of the intense demands of emotional labour in early childhood education and care work.